2006
DOI: 10.1038/nphys444
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement and the foundations of statistical mechanics

Abstract: We consider an alternative approach to the foundations of statistical mechanics, in which subjective randomness, ensemble-averaging or time-averaging are not required. Instead, the universe (i.e. the system together with a sufficiently large environment) is in a quantum pure state subject to a global constraint, and thermalisation results from entanglement between system and environment. We formulate and prove a "General Canonical Principle", which states that the system will be thermalised for almost all pure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
1,497
3
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,035 publications
(1,544 citation statements)
references
References 20 publications
37
1,497
3
7
Order By: Relevance
“…To be precise, these coefficients are chosen according to a Gaussian distribution with zero mean. Thus, the pure state |ψ is chosen according to the unitary invariant Haar measure [68,69] and, according to typicality [70][71][72][73][74][75], a representative of the statistical ensemble. The pure state |ψ , and each |ψ N , correspond to the limit of high temperatures β → 0.…”
Section: Dynamical Quantum Typicality a Conceptmentioning
confidence: 99%
“…To be precise, these coefficients are chosen according to a Gaussian distribution with zero mean. Thus, the pure state |ψ is chosen according to the unitary invariant Haar measure [68,69] and, according to typicality [70][71][72][73][74][75], a representative of the statistical ensemble. The pure state |ψ , and each |ψ N , correspond to the limit of high temperatures β → 0.…”
Section: Dynamical Quantum Typicality a Conceptmentioning
confidence: 99%
“…[17]) ‡ to get the partial fraction decomposition of the function in Eq. (22). This way one expresses the ‡ LCV whishes to thank Pierre-Yves Gaillard for pointing out this connection.…”
Section: General Casementioning
confidence: 99%
“…The Lipschitz constant of the function A (φ) = φ|A|φ has been calculated in [22] Appendix A (see also [4]) where it has been shown that |A (φ 1 ) − A (φ 2 )| ≤ 2 A op ||φ 1 − |φ 2 | where A op is the operator norm of A (maximum singular value). In our case A = |1 1| so A op = 1 and we may take η = 2 in eq.…”
Section: Random Guessmentioning
confidence: 99%
See 1 more Smart Citation
“…is an exact bound for the random Lévy random processes that form the (canonical) basis of our approach, and this formally sets the accuracy of approximating the electron spin correlators via a system consisting of N = 8 nuclei [53]. Furthermore, the values of the Hyperfine interaction couplings in (7) can be randomly picked between 0 μeV and 0.09873 μeV (as we did for this analysis) without significantly impacting on the accuracy of the spin correlator measurements, i.e., the dominant source of error is the size of the spin bath which yields an error of 6%.…”
Section: Discrete Fourier Transformmentioning
confidence: 99%